The mediating role of personality traits and internet addiction among medical students: a mediation analysis of demographic and behavioral factors - Zhang, Qiong; Huang, Linsheng; Li, Fei; Wang, Zhijie; Peng, Wei; Li, Yue; Yang, Jie; Zhang, Yan; Zhu, Xiaohu; Zhu, Mengya; Liu, Xiang; Li, Feifeng (Frontiers in Education, 2025)
Internet addiction (IA) has emerged as a significant public health concern, particularly among adolescents and university students. This study investigates the complex relationships between personality traits, demographic/behavioral factors, and IA severity among 1,182 medical students. Utilizing cross-sectional study, we assessed IA prevalence, administered validated scales (Chinese Internet Addiction Scale and Big Five Personality Inventory), and conducted mediation analyses to identify indirect pathways. Results revealed an 18.8% IA prevalence, with neuroticism, extraversion, and agreeableness exhibiting the strongest associations with IA severity. Mediation analyses highlighted extraversion and agreeableness as significant mediators between behavioral factors (e.g., proactive family support-seeking, social activity patterns) and IA, with agreeableness showing heightened susceptibility to demographic moderation. Sophomore students demonstrated peak vulnerability (26.8% IA rate), while team activity participation reduced IA risk (57.4% vs. 45.9%). The findings underscore the bidirectional influence of personality-environment interactions, emphasizing the need for tailored interventions that integrate intrinsic traits and contextual moderators. This study advances understanding of IA etiology by elucidating the mediating mechanisms linking personality architecture to behavioral outcomes, offering actionable insights for mitigating IA in academic populations.